KAJIAN PSIKOLOGI SASTRA PADA NOVEL RUMAH UNTUK ALIE KARYA LENN LIU DAN IMPLIKASINYA TERHADAP PEMBELAJARAN SASTRA DI SMA - Fatin Nadhiroh AR; Sopyan Sauri; Henri Henriyan Al Gadri (Program Studi Pendidikan Bahasa dan Sastra Indonesia, FKIP, Universitas Halu Oleo Kampus Bumi Tridharma Andounohu Kendari, Provinsi Sulawesi Tenggara – Indonesia, 2026)
This study describes the intrinsic elements and personality structure of the main character, as well as the use of Lenn Liu's novel Rumah untuk Alie as a literature learning material in high school. The method used is descriptive qualitative with content analysis and a Freudian psychoanalytic approach. Data in the form of narrative excerpts and dialogue are analyzed to identify intrinsic elements as well as the main character's id, ego, and superego. The results show that this novel has a theme of inner struggle, a mixed plot, complex characters, a socio-psychological setting, a third-person perspective, an expressive style, and a message of perseverance. The main character's personality structure includes the id (14 elements), ego (18 elements), and superego (12 elements). The use of Freud psychoanalysis to analyze lirerary works is still rarely applied at the high school level. This study is relevant for use in high school literature learning according to the Merdeka Curriculum to foster empathy, critical thinking, and literary appreciation.